Employer and new graduate satisfaction with new graduate performance in the workplace within the first year following convocation from the Ontario Veterinary College - Butler, Daniel G. (2003)
Mailed questionnaires administered to employers of graduates and to graduates of the Ontario Veterinary College in 2000 and 2001, 7 to 10 months after convocation, surveyed new graduate performance in the workplace. Proficiency at 9 species-specific (in 4 practice contexts) and 7 nonspecies-specific clinical activities were rated as “high,” “some,” or “low.” Fifteen nonvocation- specific attributes, reflecting interpersonal, communication, and business skills, and the new graduate's competence to do his/her job were rated as “very good,” “good,” or “poor.” Ninety or more percent of employers reported “high” to “some” proficiency in 8/9, 5/9, 3/9, and 1/9 activities relative to small animal, food animal, equine, and exotic animal practice, respectively, and in 5/7 nonspecies-specific clinical activities. Ninety or more percent of employers assessed workplace proficiency as “very good” to “good” in 13/15 nonvocation-specific work skills and overall competence to do the job for which the new graduate had been hired.